Effects of L-Arginine on Seizure Behavior and Expression of GFAP in Kainic Acid-Treated Rats - Sun, Yi.; Yin, Sh.; Li, Sh.; Yu, D.; Gong, D.; Xu, J.; Lian, Yo; Sun, Ch (Нейрофизиология, 2013)
Rats i.p. injected once with 10 mg/kg kainic acid exhibited clear seizure behavior (“wet-dog shakes,” rearing on the hindlimbs, and bilateral clonus). Pretreatment with L-arginine (L-Arg twice a day for 5 days) significantly decreased these manifestations. The medium dose of L-Arg (40 mg/kg) was found to be close to optimum; 10 and 160 mg/kg L-Arg provided much smaller positive effects. In KA-treated rats, a much higher density of GFAP positive astrocytes was found in the hilus of the dorsal hippocampus, while 40 mg/kg L-Arg+KA-treated rats demonstrated noticeably weaker GFAP overexpression. The results of Western blotting analysis were fully comparable with those obtained in the immunostaining experiments.